Combined Treatment With Carotid Endoarterectomy and Coronary Artery Bypass Grafting: A Single-Institutional Experience in 222 Patients. (August 2022) - Modugno, Pietro; Picone, Veronica; Centritto, Enrico Maria; Calvo, Eugenio; Canosa, Carlo; Piancone, Felice; Testa, Nicola; Camposarcone, Nicola; Castellano, Gaetano; Astore, Pasquale; Di Martino, Luigi; Di Iusto, Fabrizio; et al.
Introduction: Carotid atherosclerotic disease is a known independent risk factor of post operative stroke after coronary artery bypass grafting (CABG). The best management of concomitant coronary artery disease and carotid artery disease remains debated. Current strategies include simultaneous carotid endoarterectomy (CEA) and CABG, staged CEA followed by CABG, staged CABG followed by CEA, staged transfemoral carotid artery stenting (TF-CAS) followed by CABG, simultaneous TF-CAS and CABG and transcarotid artery stenting. Methods: We report our experience based on a cohort of 222 patients undergoing combined CEA and CABG surgery who come to our observation from 2004 to 2020. All patients with >70% carotid stenosis and severe multivessel or common truncal coronary artery disease underwent combined CEA and CABG surgery at our instituion. 30% of patients had previously remote neurological symptoms or a cerebral CT-scan with ischemic lesions. Patients with carotid stenosis >70%, either asymptomatic or symptomatic, underwent CT-scan without contrast media to assess ischemic brain injury, and in some cases, if necessary, CT-angiography of the neck and intracranial vessels. Results: The overall perioperative mortality rate was 4.1% (9/222 patients). Two patients (.9%) had periprocedural ipsilateral transient ischemic attack (TIA) which completely resolved by the second postoperative day. Two patients (.9%) had an ipsilateral stroke, while 7 patients (3.2%) had a stroke of the controlateral brain hemisphere. Two patients (.9%) patients were affected by periprocedural coma caused by cerebral hypoperfusion due to perioperative heart failure. There were no statistically significant differences between patients in Extracorporeal Circulation (ECC) and Off-pump patients in the onset of perioperative stroke. Conclusion: Our experience reported that combined surgical treatment of CEA and CABG, possibly Off-Pump, is a feasible treatment procedure, able to minimize the risk of post-operative stroke and cognitive deficits.